Evaluasi Incident Management dan Problem Management pada Bank Mandiri Unit Electronic Channel Operations (ECO) Region IX Kalimantan Menggunakan Framework ITIL V3 Domain Service Operation - Widhi Asih Paramesti; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The world of banking develops according to recent advancements in technology which focuses on improving the quality of service by transitioning from conventional transaction to electronic-based service (e-channel). The Electronic Channel Operations (ECO) of Bank Mandiri in Region IX Kalimantan is one of the operational units that run the e-channel service, especially in ATMs and EDCs for users in Kalimantan. Based on the achievement reviews in the November 2018 period, in the operational activities, there were indicators that achieved an SLA and there a few indicators that did not achieve SLA. One of the indicators were based on how well the incident was resolved and if it achieved SLA towards the users. In order to support the completion of performance achievement of an incident, l, therefore a measurement of how ready the service provider operations are needed, especially in incident management and problem management. This research utilized a framework which is considered a best practice on IT management services which is ITIL version with Service Operation Domain. Based on the analysis of the rate readiness of the Service Operation Domain which has an average score of 2.42 or equal to level 2 (Repeatable). However, to ensure that every activity in the service operations was defined entirely in the procedure and could be communicated to every staff member, therefore it needs to be raised to level 3 or equal to the defined level. The aim of providing recommendations to Region IX's Eco Unit is to improve the current readiness rate and to optimize the IT service management on the electronic channel.